Edukasi Masyarakat dalam Mendukung Pelestarian Situs Bulu Matenre sebagai Destinasi Wisata Budaya Berbasis Komunitas di Kabupaten Soppeng - Muh Rusdi; Ratna; Sri Wahyuni (PADAIDI: Journal of Tourism Dedication, 2025)
Bulu Matenre Cultural Site in Mattabulu Village, Soppeng Regency, South Sulawesi, is a cultural heritage asset with historical, religious, and tourism values. However, limited public understanding regarding cultural heritage conservation and sustainable tourism management remains a challenge in optimizing the site's potential. This community service program aimed to increase community awareness and participation in preserving the Bulu Matenre Cultural Site through educational activities, technical guidance, and community empowerment. The methods employed included field observation, stakeholder interviews, educational counseling, technical assistance, and installation of directional and informational signage. The activities involved village officials, tourism awareness groups (Pokdarwis), youth organizations, local community leaders, and tourism stakeholders. The results indicated increased public understanding of the historical significance of the site, strengthened community participation in conservation efforts, and improved tourism support facilities through the provision of information boards and directional signs. The program also generated recommendations for strengthening local human resources, improving tourism infrastructure, and enhancing collaborative governance among government agencies, educational institutions, and local communities. This initiative demonstrates that community-based educational approaches can contribute significantly to cultural heritage preservation while supporting sustainable tourism development in rural destinations.